The Effect of Brand Awareness and Eco Label on Purchase Intention of Le Minerale among Islamic Economics Students: Ignoring the Price Factor? - Setiawan, Alwan; Padmasari, Intan; Hulaemah, Eem (Jurnal Riset Akuntansi Terpadu, 2025)
The bottled water (AMDK) industry in Indonesia has experienced significant growth in line with theincreasing public awareness of the importance of safe and convenient drinking water. One of the brandsthat has gained consumer attention is Le Minerale. This study aims to analyze the influence of brandawareness, price, and eco-label on the purchase intention of Le Minerale products among Islamiceconomics students in Java. The research employs a quantitative approach with random samplingtechniques, involving 80 respondents from several provinces. Data analysis was performed using logisticregression to evaluate the effect of independent variables on the dependent variable. The results showthat brand awareness and eco-label significantly influence students' purchase intention, with odds ratiosof 2.3 and 2.15 times higher, respectively, for students who are more aware of the brand and eco-labelcompared to those who are not. On the other hand, the price variable does not significantly influencepurchase intention. These findings indicate that brand awareness and environmental concerns are keyfactors in driving purchasing decisions in the segment of Islamic economics students. This researchcontributes to the development of environmentally-friendly marketing strategies relevant for companiesto increase their market share.